Упростите выражение
(x+3y)(x+y+ 2) - (x+y)(x+3y + 2)=
, заранее

azamaaaaa azamaaaaa    3   22.11.2021 10:58    0

Ответы
Mixail1510 Mixail1510  22.11.2021 11:00

Объяснение:

(x+3y)(x+y+ 2) - (x+y)(x+3y + 2)=x²+3xy+xy+3y²+2x+6y-(x²+xy+3yx+3y²+2x+2y)=

= приведем подобные=

=x²+4xy+3y²+2x+6y-(x²+4yx+3y²+2x+2y)=раскроем скобки=

=x²+4xy+3y²+2x+6y-x²-4yx-3y²-2х-2у=сократим на x² =

=4xy+3y²+2x+6y-4yx-3y²-2х-2у=сократим на 4xy =

=3y²+2x+6y-3y²-2х-2у=сократим на 3y²=

=2x+6y-2х-2у=сократим на 2x=

=6y--2у=4у

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра